Farmers’ knowledge, attitudes, and practices toward animal welfare across different beef cattle farming systems in Phayao Province, Thailand - Kongmuang, Nattamaporn; Intawicha, Payungsuk; Sakphoowadon, Surinthip; Saengwong, Sureeporn (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to evaluate the knowledge, attitudes, and practices (KAP) toward animal welfare principles of beef cattle farmers using different farming systems in Phayao Province, Thailand. Materials and Methods: A structured questionnaire survey was conducted among farmers using extensive (n = 20), semi-intensive (n = 20), and intensive systems (n = 20). Descriptive statistics were employed to describe the demographic characteristics and KAP. Chi-square tests were performed to evaluate the relationships between farming systems and KAP variables. The multivariate influences of the farming system on the overall KAP scores were assessed using a multivariate analysis of variance (MANOVA). Pearson’s correlation coefficients were used to examine the relationships among the KAP components. Results: The chi-square test revealed significant differences (p < 0.001) in KAP among farming systems. Intensive farmers showed the highest levels of knowledge (100% good), positive attitudes (55%), and very good practices (80%). However, extensive farmers exhibited lower knowledge (45%), moderate attitudes (90%), and poor practices (95%). MANOVA found that KAP levels were significantly influenced by farming systems (p < 0.001). Pearson’s correlation analysis showed significant positive correlations among the KAP components. Attitudes strongly influenced welfare practices (r = 0.93, p < 0.001), while knowledge revealed positive correlations with both attitudes (r = 0.73, p < 0.001) and welfare practices (r = 0.69, p < 0.001). Conclusion: This study highlights the importance of specific programs, including farmer education, training, and infrastructure development, for improving animal welfare compliance across several farming systems. J. Adv. Vet. Anim. Res., 12(3): 861–869, September 2025 http://doi.org/10.5455/javar.2025.l948